2011
DOI: 10.3109/09638288.2011.585212
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing healthy aging with multiple sclerosis: a qualitative study

Abstract: This two-tiered conceptual model of health aging, based on the perspectives of older persons with MS, provides a potential framework for the development of MS self-management program curricula aimed at optimizing quality of life. Further empirical testing may validate its utility in predicting healthy aging with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…Elderly individuals with MS have reported their ability to adapt and adjust to MS over many years, and being independent and remaining at home is highly valued. 37 These results are similar to the findings from the Sonya Slifka Longitudinal Multiple Sclerosis Study, in which it was shown that patients over age 65 years often lived alone but viewed their health status positively, thus appearing to adapt over time despite the progression of disease. 17 This sample of patients was slightly different from the overall MS population, as women made up 80% of this study, compared with approximately 66% of the overall MS population.…”
Section: Ms Clinical Characteristicssupporting
confidence: 85%
See 2 more Smart Citations
“…Elderly individuals with MS have reported their ability to adapt and adjust to MS over many years, and being independent and remaining at home is highly valued. 37 These results are similar to the findings from the Sonya Slifka Longitudinal Multiple Sclerosis Study, in which it was shown that patients over age 65 years often lived alone but viewed their health status positively, thus appearing to adapt over time despite the progression of disease. 17 This sample of patients was slightly different from the overall MS population, as women made up 80% of this study, compared with approximately 66% of the overall MS population.…”
Section: Ms Clinical Characteristicssupporting
confidence: 85%
“…55 As individuals with MS age, they are likely to have the same comorbidities as the general population, including hypertension, heart conditions, diabetes, and even thyroid disease. 37 These comorbidities may also lead to other related illnesses. Ploughman et al 37 reported that older people with MS are very concerned about comorbid conditions and the effects on their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to describe healthy aging from the perspective of the older person with MS, researchers interviewed 18 people who were 55 years of age and older with symptoms for 20 or more years. 54,55 Analysis of key themes emerging from the data showed that older people with MS highly valued four major factors that they felt contributed to health and life satisfaction as they aged 54 : work and social engagement, effective and accessible health care, healthy lifestyle habits, and maintaining independence at home.…”
Section: Research On Aging and Older Adults With Multiple Sclerosismentioning
confidence: 99%
“…Based on clinical experience throughout the continuum of care and findings from qualitative research, [54][55][56] we know that fall circumstances change as one ages with MS and depend on mobility level 55 (Figure 1). During interviews with older people with MS, participants did not identify themselves vention intervention?"…”
Section: Fall Circumstances Vary Depending On Disabilitymentioning
confidence: 99%